MicroRNAs 296 and 298 are imprinted and part of the GNAS/Gnas cluster and miR-296 targets IKBKE and Tmed9 - Robson, Joan E. (Cold Spring Harbor Laboratory Press, 2012)
Genomic imprinting is the phenomenon whereby a subset of genes is differentially expressed according to parental origin. Imprinted genes tend to occur in clusters, and microRNAs are associated with the majority of well-defined clusters of imprinted genes. We show here that two microRNAs, miR-296 and miR-298, are part of the imprinted Gnas/GNAS clusters in both mice and humans. Both microRNAs show imprinted expression and are expressed from the paternally derived allele, but not the maternal allele. They arise from a long, noncoding antisense transcript, Nespas, with a promoter more than 27 kb away. Nespas had been shown previously to act in cis to regulate imprinted gene expression within the Gnas cluster. Using microarrays and luciferase assays, IKBKE, involved in many signaling pathways, and Tmed9, a protein transporter, were verified as new targets of miR-296. Thus, Nespas has two clear functions: as a cis-acting regulator within an imprinted gene cluster and as a precursor of microRNAs that modulate gene expression in trans. Furthermore, imprinted microRNAs, including miR-296 and miR-298, impose a parental specific modulation of gene expression of their target genes.